Tobacco Smoking and Cutaneous Squamous Cell Carcinoma: A 16 -Year Longitudinal Population-Based Study - McBride, Penelope (2011)
BACKGROUND: Although tobacco smoking is commonly cited as a risk factor for cutaneous squamous cell carcinoma (SCC), the evidence from previous clinical and case-control studies is conflicting. We therefore aimed to prospectively examine the role of tobacco smoking in the development of SCC of the skin in a population-based study. METHODS: Study participants were 1287 adults aged 25 to 75 years in 1992, randomly selected from the Nambour community, with no previous history of SCC. Standard skin pigment and sun-sensitivity profiles were obtained at baseline. Detailed prospective information on sun exposure, smoking and skin cancer occurrence (histologically-confirmed) was collected over a 16-year period, 1992-2007. RESULTS: Of 1287 participants, 43% were male, and average age was 48 years. A total of 188 first cutaneous SCCs were identified during the study period. After adjustment for other known risk factors, neither former nor current smokers were at raised risk of SCC: RR 1.1, 95%CI 0.8, 1.5 and RR 1.1, 95%CI 0.7, 1.5, respectively, compared with lifelong non-smokers, nor were there any dose-response relationships with amount smoked or duration of smoking and risk of SCC. CONCLUSIONS: In this Australian follow-up study tobacco smoking did not increase the risk of SCC of the skin. IMPACT: These prospective adjusted data provide strong evidence which suggests that cutaneous SCC should not be on the list of tobacco-related cancers.